Diversidade dos efeitos clínicos da Hemofilia A: influência de variantes genéticas e avaliação global da hemostasia - Fernanda Martins Lott Fonseca (2018)
Hemophilia A is an X-linked hemorrhagic disorder that affects 1-2 boys born alive worldwide. This disorder is characterized by the decrease of circulating Factor VIII in plasma and is classified according to the activity resulting from this factor in severe, moderate and mild. It is known that there is a heterogeneity of clinical manifestations, bleeding and consumption of Factor VIII, among individuals with the same classification of hemophilia. This study aims to investigate mutations and polymorphisms of coagulation proteins that could influence the clinical diversity of patients with moderate and severe haemophilia and to determine verify the thrombin generation potential of these patients. The study included 51 patients with moderate (n = 13) and severe (n = 38) haemophilia A attended at the Hemominas Foundation and 37 blood donors, as a control group. We have performed analysis of the clinical data of the patients, genotyping of the Factor V Leiden (G1691A), Prothrombin (G20210A), Factor VII (G10976A), Protein C (A-1641G and A-1476T) and of Protein S (A2148G), and thrombin generation test. To investigate the influence of the genetic variants, the patients were distributed in two groups, low and high hemorrhagic profiles, according to factor VIII consumption, in U / kg / year. No differences were found in the allelic frequencies of the genetic variants between the two groups. The thrombin generation of the patients was significantly lower than that of the controls, but there was no difference between the thrombin generation of the two groups of patients, in relation to the hemorrhagic profile. In contrast, there was a significant difference in thrombin generation parameters between patients with non-O and O blood types. It was concluded that the presence of genetic variations in the genes of the proteins involved in the coagulation and natural anticoagulation ,and the potential of thrombin generation did not influence hemorrhagic manifestations of patients with moderate and severe hemophilia A. This study was performed in a limited number of samples, therefore new studies should be done in a more robust sample to investigate factors that contribute to the clinical variety of patients with hemophilia A.